Pengaruh Gaya Kepemimpinan dan Motivasi Kerja terhadap Kinerja Karyawan PT. BPR BKK TASIKMADU (Perseroda) Kantor Cabang Jumantono Kabupaten Karanganyar - Rosita Dewi; Winarti Winarti; Damayanti Suhita (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Leadership in an organization is considered a turning point and central in improving employee performance. A leader's approach to directing, motivating, and managing a team can be achieved through leadership style. Moreover, work motivation also becomes a driving factor in enhancing employee performance within an institution or company. PT. BPR BKK TASIKMADU (Perseroda) Jumantono branch has experienced changes in target achievements in each period, which sparked the researcher’s interest in conducting this study. The objective of this research is to determine the influence of leadership style and work motivation variables on employee performance at PT. BPR BKK TASIKMADU (Perseroda) Jumantono branch, Karanganyar Regency. This research uses a quantitative method, utilizing leadership style theory by Kartini Katono, work motivation theory by Abraham Maslow, and employee performance theory by Robbins. The study includes the entire population, which consists of 16 employees of PT. BPR BKK TASIKMADU (Perseroda) Jumantono branch. The data analysis technique used is multiple linear regression. The results show a strong relationship between leadership style and work motivation. Leadership style obtained a t-value of 6.085, while work motivation scored 2.727, indicating that both variables significantly influence employee performance. Leadership style and work motivation simultaneously influence employee performance, with an F-value of 35.143.